2016
DOI: 10.1186/s12889-016-3358-5
|View full text |Cite
|
Sign up to set email alerts
|

Precarious employment is a risk factor for poor mental health in young individuals in Sweden: a cohort study with multiple follow-ups

Abstract: BackgroundThe globalisation of the economy and the labour markets has resulted in a growing proportion of individuals who find themselves in a precarious labour market situation, especially among the young. This pertains also to the Nordic countries, despite their characterisation as well developed welfare states with active labour market policies. This should be viewed against the background of a number of studies, which have shown that several aspects of precarious employment are detrimental to mental health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
96
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(114 citation statements)
references
References 38 publications
12
96
0
6
Order By: Relevance
“…A recent review concluded that the majority of surveys on employment insecurity are related to self-reported mental health (Llosa-Fernández et al 2018), borne out by previous studies showing that mental health was worse among young, non-regularly employed workers and employment insecurity may be particularly large in this group (Canivet et al 2016;Vancea and Utzet 2017). There has been no research that has yet evaluated the employment insecurity of non-regularly employed researchers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent review concluded that the majority of surveys on employment insecurity are related to self-reported mental health (Llosa-Fernández et al 2018), borne out by previous studies showing that mental health was worse among young, non-regularly employed workers and employment insecurity may be particularly large in this group (Canivet et al 2016;Vancea and Utzet 2017). There has been no research that has yet evaluated the employment insecurity of non-regularly employed researchers.…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that non-regular employment has a large impact on mental health specifically among young age groups. In a study of workers aged 18-34 in Sweden, the experience of non-regular employment significantly increased the incidence of mental health problems (Canivet et al 2016). A meta-analysis of studies examining the 18 to 35 years age range in Europe showed that young people with non-regular employment are at increased risk for mental health disorders (Vancea and Utzet 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The growth of precarious work among professionals, including pharmacists, has been documented in many countries such as the United Kingdom . Precarious work was shown to be a risk factor of poor mental health among young professionals …”
Section: Introductionmentioning
confidence: 99%
“…Unemployment might concur with poor mental health [63, 64]. Precarious employment was a risk factor for subsequent development of mental health problems [65]. There was an increase in poor mental health among immigrant workers experienced deterioration in employment conditions [66].…”
Section: Discussionmentioning
confidence: 99%